Morphology and tensile property of the blow molded high density polyethylene (HDPE) and cross-linked HDPE bottles after immersion in petrol and diesel - Chen, C. H. (2004)
Polymer are frequently brought into contact with liquids such as chemical products, motor fuels and lubricants because of their varied applications. The effect of petrol and diesel for a period of time on High Density polyethylene (HDPE) and cross-linked HDPE bottles is studied according to ISO 175: 1999. The HDPE and cross-linked HDPE bottles were prepared by blow molding technique. The bottles were immersed in petrol and diesel for I day, 1 week and 16 weeks before undergoing tests. The temperature for the immersion test used was 23°C and 70°C. Tensile test was carried out to determine the modulus, tensile strength and elongation at break The tensile properties results show that the rate of degradation for petrol immersion > diesel immersion and temperature 70°C > 23°C for both HDPE and XLHDPE. The cross-linked HDPE is more stable to petrol and diesel attack compared to HDPE. These phenomena correlate with the surface morphology shown by the micrograph. Surface inspection for the morphology property was observed using Scanning Electron Microscopy (SEM). Micrograph analysis showed that the degraded samples undergo brittle failure whereas undergraded samples experienced ductile failure.